PENGARUH DIGITAL MARKETING,BRAND IMAGE, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE DI APLIKASI TOKOPEDIA - Dyany Mahatmya Dite Sasri (2020)
The technology development in this era makes a lot of changes, one of them is a lot of companies who create business ideas by using the internet. This makes a lot of e-commerce that currently exists in Indonesia, which is one of the factors that cause the change of society's lifestyles is by making purchase decision in the e-commerce in Indonesia one of them is Tokopedia.One of the products that is currently buying by the consumers is smartphone, because there is a lot of ease that the internet can given by using smartphone. The research that has been done is quantitative research. The purpose of this research is to dertermine whether the decision to purchase smartphone product in the Tokopedia application is influenced by digital marketing, brand image and price. The population in this research are users and smartphone buyers in the Tokopedia application. The sample used was 75 respondent, using probability sampling techniques and the simple random sampling method in taking the sampel. The analysis technique used is PLS (Partial Least Square) by using SmartPls 3.3.2 Software. The result obtained in this research are digital marketing and price have a significant influence on purchasing decisions. As for the brand image itself, it has no influence and is not significant on purchasing decisions